A framework for transparency in international trade - Paloma Bernal Turnes; Ricardo Ernst (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
The aim of this paper is to cover the gap in literature about transparency in the context of international trade facilitation. It focuses on the importance of transparency in achieving growth in international trade and the differences between non-transparent practices and corruption in global trade. Managing the disclosure of information about rules, regulations and laws is not the only trade policy instrument where transparency becomes important. To build a framework on levels of transparency we developed a matrix classifying the transparency of each country based on ease of doing business and levels of bribery. Four different strategies are explained based on the different scenarios of transparency in international trade. The main conclusions reflect that disclosure of information is not enough to guarantee transparency and monitoring of transparency must be improved.
Keywords: F13; F18; D73; 330; Transparency; Accountability; International trade; Corruption; Bribery; Trade facilitation